SUNAT PEREMPUAN DALAM PERSPEKTIF FIKIH - Afifi Fauzi Abbas; Mona Eliza (Tamaddun, 2018)
In 2008 the MUI issued a fatwa related to female circumcision, namely fatwa number 94 "Fatwa on Prohibition of Circumcision Against Women", which states that the legal status of female circumcision is makrumah, something that is considered good and recommended. In many studies it was found that female circumcision is just a tradition, not a religious order. In Indonesia, 28% of female circumcision practices are only symbolic, 49% are done in the form of slicing or stabbing and 22% in the form of cutting. This means that 71% of the practice leads to endangering women, mainly because it is not carried out by medical personnel and uses tools that are not sterile. The Hanafi, Maliki and Hanbali schools place women's circumcision laws in the sunnah or makrumah / glory laws for women. The Syafii School believes that female circumcision is obligatory as a law for men. Although the various Islamic scholars have different opinions about the law of female circumcision, none of them prohibits the practice of female circumcision.